2013
DOI: 10.1002/jgra.50103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of low‐altitude ENA emissions in two substorms

Abstract: We report on the dynamics of low‐altitude energetic neutral atom (ENA) emissions during two substorms that occurred during the main phases of two storms: (1) a CIR‐driven storm on 11 October 2008 and (2) a coronal mass ejection (CME)‐driven storm on 5 April 2010. For both of these storms, we have complementary spacecraft and ground‐based observations. The dual‐spacecraft Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) mission obtained ENA images containing low‐altitude emissions (LAEs). Substorm dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
(75 reference statements)
2
19
0
Order By: Relevance
“…Results from the initial processing of the data indicate reasonable distributions that agree with prior studies [ Søraas and Aarsnes , ; Pollock et al , ; Buzulukova et al , ; Vorobjev and Yagodkina , ]. The combined pitch angles appear centered slightly above 90°, which for nearly mirroring neutrals escaping the atmosphere is expected.…”
Section: Lae Pixel Distributionssupporting
confidence: 84%
“…Results from the initial processing of the data indicate reasonable distributions that agree with prior studies [ Søraas and Aarsnes , ; Pollock et al , ; Buzulukova et al , ; Vorobjev and Yagodkina , ]. The combined pitch angles appear centered slightly above 90°, which for nearly mirroring neutrals escaping the atmosphere is expected.…”
Section: Lae Pixel Distributionssupporting
confidence: 84%
“…A ring current model can be considered as a bounce-averaged kinetic code and normally operates with a large number (from hundreds to thousands) of "species", i.e., distributed in energy, pitch angle, or first and second adiabatic invariants. Currently, there are several major ring current models used by the community: the standard Rice Convection Model (RCM) (Harel et al, 1981;Toffoletto et al, 2003) or the RCM-E, a version that includes frictional dissipation (Lemon et al, 2003;Chen et al, 2015); the Magnetospheric Specification Model (MSM) (Wang et al, 2003(Wang et al, , 2004; the Comprehensive Ring Current Model (CRCM) (Fok et al, 1993(Fok et al, , 1995(Fok et al, , 2001(Fok et al, , 2014 and its successor, the Comprehensive Inner Magnetosphere-Ionosphere model (CIMI) (Fok et al, 2014); the Ring current-Atmosphere interactions Model (RAM) (Jordanova et al, 1994(Jordanova et al, , 2001 and its extended version with magnetic equilibrium solver Zaharia, 2008); the Hot Electron and Ion Drift Integrator (HEIDI) code (Liemohn et al, 1999); and the Inner Magnetosphere Particle Transport and Acceleration model (IMPTAM) (Ganushkina et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Valek et al (2010) showed that LAEs respond quickly to geomagnetic activity and are more dynamic than the ring current emissions (RCEs). In a follow-up study, Buzulukova et al (2013) showed that LAEs first increase during the substorm growth phase when RCEs may be on the edge of detectability and concluded that the parent ions responsible for these LAEs originated in the near-Earth tail region. It follows from these studies that the global ion precipitation in the near-Earth region will be reflected in the LAE index.…”
Section: Global Observations: Twins and Amperementioning
confidence: 99%
“…For ions, this condition may be satisfied under several sets of circumstances. During storms and substorms, injections can transport ions with isotropic pitch angle distributions into the nightside inner magnetosphere, filling the loss cone (Buzulukova et al, ; Fok et al, ; Moore & Arnoldy, ; Valek et al, ). Trapped ions can also be pitch angle scattered into the loss cone by Coulomb collisions or wave‐particle interactions (Cornwall et al, ; Fok et al, , ; Frey et al, ; Gary et al, ; Williams & Lyons, ; Yuan et al, ).…”
Section: Ion Precipitationmentioning
confidence: 99%